The Invisible College of International Lawyers in Private International Law Today - Hess , Burkhard; Requejo Isidro, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
These pages elaborate briefly on Oscar Schachter’s celebrated reflections about an invisible college of international lawyers, with a focus on today’s private international law.
Keywords: “Invisible college”; law-making processes; professional community of international scholars; Hague Convention 2019